Integration of metabolomics and transcriptomics identifies pathways involved in intermittent fasting and renal injury induced by a high-fat diet in mice - Yuan, Lingfeng; Song, Xiaobo; Luan, Yisheng; Hong, Weihao; Hu, Yue; Ding, Shuqiao; Zhang, Bing; Xiong, Yingzhe (Frontiers in Physiology, 2025)
Obesity, a worldwide epidemic, is often accompanied by renal dysfunction or accelerating kidney disease. Intermittent fasting (IF) has become a popular weight loss approach, but the data for obesity-related kidney disease are very limited. Moreover, there is currently no combined omics study on its related metabolism, mechanisms, and pathways. The purpose of this study was to examine the preventive effect of IF on renal injury induced by a high-fat diet (HFD) and to explore the related pathways based on an omics analysis. We used an HFD to induce obesity-related renal injury. During IF intervention, the mice were allowed free access to regular chow every other day and were not provided food on the other day. Our result found that IF could effectively prevent obesity-related renal injury in glomerular morphological changes and urine components. Metabolomic and transcriptomic analyses revealed that IF affected the thermogenesis pathway, cholesterol metabolism pathway, and glycerolipid and glycerophospholipid metabolism pathways, and prevented and alleviated obesity-related renal injury through inflammation pathways and the insulin resistance pathway. This research would provide valuable data for the prevention and treatment of kidney diseases related to obesity.